2022
DOI: 10.2147/dddt.s347297
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and CRISPR Cas Systems: Potential Cure of COVID-19?

Abstract: The COVID-19 has plunged the world into a pandemic that affected millions. The continually emerging new variants of concern raise the question as to whether the existing vaccines will continue to provide sufficient protection for individuals from SARS-CoV-2 during natural infection. This narrative review aims to briefly outline various immunotherapeutic options and discuss the potential of clustered regularly interspaced short palindromic repeat (CRISPR Cas system technology against COVID-19 treatment as speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 210 publications
0
3
0
Order By: Relevance
“…CRISPR-Cas systems are proposed by researchers to degrade the viral genome of SARS-CoV-2, which could also inspire methods against GBM by degrading the genome of glioblastoma cells. However, suitable delivery system into the glioblastoma cells should be found, for instance, viral vectors or delivery system that enters the GCs by binding with its cell surface receptors [ 135 ]. CRISPR-Cas systems can be applied a variety of functions including genetic screening, gene corrections of genetic mutations on DNA and RNA level in the oncogenesis, and maintenance pathways of GBM, in addition knocking out surface receptors of GBM cells and GSCs, also CRISPR-Cas techniques show potential in inducing GBM cellular apoptosis or breaking down GBM cell genome.…”
Section: Crispr-cas Technique Against Glioblastomamentioning
confidence: 99%
“…CRISPR-Cas systems are proposed by researchers to degrade the viral genome of SARS-CoV-2, which could also inspire methods against GBM by degrading the genome of glioblastoma cells. However, suitable delivery system into the glioblastoma cells should be found, for instance, viral vectors or delivery system that enters the GCs by binding with its cell surface receptors [ 135 ]. CRISPR-Cas systems can be applied a variety of functions including genetic screening, gene corrections of genetic mutations on DNA and RNA level in the oncogenesis, and maintenance pathways of GBM, in addition knocking out surface receptors of GBM cells and GSCs, also CRISPR-Cas techniques show potential in inducing GBM cellular apoptosis or breaking down GBM cell genome.…”
Section: Crispr-cas Technique Against Glioblastomamentioning
confidence: 99%
“… • Low levels of nAb after two or three doses of vaccination • SARS-CoV-2 variants showed partial vaccine escape, especially the Omicron variant (BA.1) compared to the Delta variant (B.1.617.2) • Resistance to anti-SARS-CoV-2 mAb [ 289 ] ALVR109 * Alpha, Beta, Gamma, Delta, Epsilon, and Kappa N.A • On day 10 after the second injection of ALVR109, the patient`s nasopharyngeal SARS-CoV-2 viral load became persistently untraceable • After the second infusion, the patient was discharged on minimal oxygen support and received a second negative result of quantitative nasopharyngeal PCR [ 290 ] CAR-NK cell therapy * SARS-CoV-2 variant Leukemia and MM • CAR-NK cells target SARS-CoV-2 spike protein with CR3022 scFv domain, a potent neutralizing antibody targeting SARS-CoV-2 S protein • The results showed that CR3022-CAR-NK cells can kill SARS-CoV-2 infected cells in vitro [ 291 ] Inhibitors PAD-4 inhibitors SARS-CoV-2 variants MM • Offers broad therapeutic potential in a wide range of inflammatory diseases such as COVID-19 through the formation of NETs • In reducing thrombotic complications in various inflammatory disorders such as COVID-19 and suggests that these inhibitors may be valuable in the treatment of immunothrombotic origin of SARS-CoV-2 [ 292 ] FLT3 inhibitors SARS-CoV-2 variant AML • Decreased autophagy can reduce the risk of chemotherapy resistance and mortality [ 293 ] SMYD2 * Delta variant N.A • Inhibition downregulates TMPRSS2 • Reduces SARS-CoV-2 infection [ 294 ] Other treatment Convalescent plasma Alpha B-cell lymphoid malignancy AML • Reduction of mortality [ …”
Section: Haematological Malignancies and Covid-19mentioning
confidence: 99%
“…Various cell types including CAR-T and CAR-NK, can be successfully modified today via CRISPR/Cas strategies. PD-1 knocking-down is a well-known strategy to circumvent the inhibitory immune system checkpoint [ 65 , 66 ]. In this method, exhausted virus-reactive CD8 + memory T cells are isolated from patients.…”
Section: Clinical Applications Of the Crispr Systemmentioning
confidence: 99%